HARMONI DALAM KEBHINEKAAN (Kearifan Lokal Masyarakat Pulau Enggano Provinsi Bengkulu Dalam Mengatasi Konflik) - Intan Permata Sari (Universitas Andalas, 2017)
Ethnic and religious conflicts are still a hot conversation in early 2017. Discourses on non-Muslim Muslims as well as indigenous non-indigenous peoples are the main topics in various news in Indonesia. Peace that has been maintained, post-conflict that occurred in Sampit and Ambon, suddenly disturbed. People in Indonesia are again divided into religious groups (Muslim or non-Muslim) or ethnic groups (indigenous or non-indigenous). However, Indonesia has the hope to make peace in the differences and make it harmony in society. We can learn from Enggano society. The people of Enggano are the people who live in one of the outer islands in Indonesia. The island is located in the west of Sumatra Island. The Enggano people are able to live in diversity even though their lives are far from prosperous, poor access and facilities, and far from the government's attention. Almost no conflict occurred on this island. This is because Enggano local wisdom is so strong that it can bridge the differences.